2020
DOI: 10.21203/rs.3.rs-121171/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interleukin-6 As An Enhancer of Anti-Angiogenic Therapy for Ovarian Clear Cell Carcinoma.

Abstract: Ovarian clear cell carcinoma (OCCC) is a subtype of epithelial ovarian cancer (EOC) and associated with elevated interleukin-6 (IL-6) expression, resistance to chemotherapy, and increased mortality. Although bevacizumab (Bev) is a widely used anti-angiogenic agent for EOC, the efficacy of Bev and the role of IL-6 in modulating angiogenesis in OCCC are unknown. We performed tube formation assays on human umbilical vein endothelial cells (HUVEC) cultured in OCCC conditioned media and in direct co-culture with OC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In addition, Seki et al. showed that IL-6 inhibition leads to reduced anti-angiogenic activity in co-cultures of ovarian clear cell carcinoma (OCCC) cells and HUVECs by increasing angiopoietin-1 (Ang1) secretion and reducing VEGF expression [ 59 ]. It can be considered that IL-6 regulates VEGF synthesis, and thus its anti-angiogenic activity may be indirect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Seki et al. showed that IL-6 inhibition leads to reduced anti-angiogenic activity in co-cultures of ovarian clear cell carcinoma (OCCC) cells and HUVECs by increasing angiopoietin-1 (Ang1) secretion and reducing VEGF expression [ 59 ]. It can be considered that IL-6 regulates VEGF synthesis, and thus its anti-angiogenic activity may be indirect.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was followed and modified as previously reported 35 . Briefly, human umbilical vein endothelial cells (HUVECs, ATCC, Cat# CRL-1730) were incubated with endothelial cell medium (ECM) (Sciencell Research Laboratory, CA, 1001) at passage 6-8 when the cells reached to 80-100% confluency.…”
Section: Methodsmentioning
confidence: 99%
“…3 Both histopathology and FIGO staging are considered the gold standard for classification of EOC subgroups and are relevant prognostic factors for stratification. 4 Many studies have explored the molecular mechanisms underlying this malignancy, 5,6 however, accurate prediction of treatment outcome and anticipated personalized prognosis is still lacking. 7,8…”
Section: Introductionmentioning
confidence: 99%
“…3 Both histopathology and FIGO staging are considered the gold standard for classification of EOC subgroups and are relevant prognostic factors for stratification. 4 Many studies have explored the molecular mechanisms underlying this malignancy, 5,6 however, accurate prediction of treatment outcome and anticipated personalized prognosis is still lacking. 7,8 Among the histotypes of EOC, ovarian clear cell carcinoma (OCCC) exhibits unique clinicopathological and molecular features, and therefore is recognized as a distinct entity, presenting unique challenges for treatment.…”
Section: Introductionmentioning
confidence: 99%